Pelatihan Menggunakan Aplikasi Inlis Lite Di Dinas Perpustakaan Daerah Praya - Munzani Munzani; Hasyim Asyari (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The use of application technology in modern libraries has played a significant role in increasing the efficiency and accessibility of library services. This study aims to describe community service carried out through the application of the Inlist Lite application at the Regional Library. Inlist Lite is a smartphone-based application specially designed to assist users in searching, borrowing and returning books online. This journal includes a description of the implementation of the Inlist Lite application in Regional Libraries, an evaluation of the impact of using the application on library operational efficiency, as well as the benefits felt by the community in accessing library services.